2017
DOI: 10.1111/1460-6984.12331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timing of delayed hard palate closure on articulation skills in 3‐year‐old Danish children with unilateral cleft lip and palate

Abstract: Background: Differing results regarding articulation skills in young children with cleft palate (CP) have been reported and often interpreted as a consequence of different surgical protocols. Aims: To assess the influence of different timing of hard palate closure in a two-stage procedure on articulation skills in 3-year-olds born with unilateral cleft lip and palate (UCLP). Secondary aims were to compare results with peers without CP, and to investigate if there are gender differences in articulation skills. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
(150 reference statements)
1
11
0
Order By: Relevance
“…Despite this, they still had poorer articulation skills than children in arm A in center 1. This finding indicates that delaying hard palate closure (arm B) until 3 years of age still has a negative effect on the developing phonological system at age 5 as previously demonstrated (Willadsen et al, 2018). The importance of this finding is underlined by the present and previous findings that children with UCLP have poorer articulation skills than children without CP (Lohmander and Persson, 2008; Klintö et al, 2014a).…”
Section: Discussionsupporting
confidence: 78%
“…Despite this, they still had poorer articulation skills than children in arm A in center 1. This finding indicates that delaying hard palate closure (arm B) until 3 years of age still has a negative effect on the developing phonological system at age 5 as previously demonstrated (Willadsen et al, 2018). The importance of this finding is underlined by the present and previous findings that children with UCLP have poorer articulation skills than children without CP (Lohmander and Persson, 2008; Klintö et al, 2014a).…”
Section: Discussionsupporting
confidence: 78%
“…This is in line with the findings of Peterson-Falzone 36 and Willadsen, Boers, Schöps, Kisling-Møller, Nielsen, Jørgensen. 37 This study showed that surgery outcomes using different surgical protocols achieved similar GOSLON ratings. 38 The UPFCD clinic displayed good treatment outcomes comparable to those of the CCUK cohort and the Americleft Study Centre C. This study outcome suggests that the clinical treatment protocol at UPFCD is an effective strategy for treating patients with UCLP regarding favourable maxillary development.…”
Section: Treatment Outcome Auditmentioning
confidence: 60%
“…Several studies reported on both cleft and developmental phonological processes (Willadsen et al . , Chacon et al . , Klintö et al .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported on both cleft and developmental phonological processes (Willadsen et al 2018, Chacon et al 2017, Klintö et al 2014a, 2014b, Willadsen 2012, Konst et al 2003, Morris and Ozanne 2003, Hutters et al 2001). This provides a broader perspective of an individual's phonological development from both a cleft and developmental perspective.…”
Section: Swedenmentioning
confidence: 99%